Carboxylated and Uncarboxylated Forms of Osteocalcin Directly Modulate the Glucose Transport System and Inflammation in Adipocytes - Hill, H. S.; Grams, J.; Walton, R. G.; Liu, J.; Moellering, D. R.; Garvey, W. T. (Hormone and Metabolic Research, 2014)
Osteocalcin is secreted by osteoblasts and improves insulin sensitivity in vivo, although mechanisms remain unclear. We tested the hypothesis that osteocalcin directly modulates cell biology in insulin-targeted peripheral tissues. In L-6 myocytes, osteocalcin stimulated glucose transport both in the absence (basal) and presence of insulin. Similarly, in primary cultured adipocytes, both carboxylated and uncarboxylated osteocalcin increased basal and insulin-stimulated glucose transport as well as insulin sensitivity. Osteocalcin also increased basal and insulin-stimulated glucose oxidation, though there was no effect on fatty acid synthesis or lipolysis. In primary-cultured adipocytes, both forms of osteocalcin suppressed secretion of tumor necrosis factor alpha into the media; however, only carboxylated osteocalcin suppressed interleukin 6 release, and neither form of osteocalcin modulated monocyte chemoattractant protein-1 secretion. Both carboxylated and uncarboxylated osteocalcin increased secretion of adiponectin and the anti-inflammatory cytokine interleukin 10. In conclusion, both carboxylated and uncarboxylated osteocalcin directly increase glucose transport in adipocytes and muscle cells, while suppressing proinflammatory cytokine secretion and stimulating interleukin 10 and adiponectin release. Thus, these results provide a mechanism for the insulin-sensitizing effects of osteocalcin and help elucidate the role that bone plays in regulating systemic metabolism.
Keywords: glucose homeostasis; metabolism; adipocyte biology